Mechanical thrombectomy for recurrent large vessel occlusion. (August 2019) - Bhogal, P.; AlMatter, M.; Hellstern, V.; Pérez, M. Aguilar; Ganslandt, O.; Bäzner, H.; Henkes, H.
Highlights: Recurrent large vessel thromboembolic stroke is rare. Cardioembolism is the most common cause for repeat large vessel occlusion. Recurrent large vessel occlusion can occur despite preventative medications. Repeat mechanical thrombectomy is safe with a low risk of complications. Haemorrhagic complications are low. Abstract: Although mechanical thrombectomy (MT) has been shown in numerous trials to be a successful treatment option for patients with large vessel occlusion (LVO), there is limited information on the safety and effectiveness of the technique in cases of recurrent LVO. To this end, we performed a retrospective review of our prospectively maintained database to identify all patients that had undergone more than one MT procedure January 2008 and January 2018. The data collected on these patients included baseline demographics and any history of diabetes mellitus, hypercholesterolaemia, hypertension, atrial fibrillation or smoking. We also recorded when the symptoms had started, the patient's NIHSS and ASPECT scores, the number of passes taken, the patient's final TICI score, any complications which arose and the patient's mRS at 90 days. Our dataset encompassed 25 patients (of which 17 (68%) were female) who had undergone a total number of 52 MT's. Average age at 1st presentation was 70 ± 12.8 years. The median time between one stroke and the next was 71 days (range 1–1059, IQR 183 days). The majority of the strokes were deemed cardioembolic (86.5%) in origin. There was no significant difference in the procedure times, number of passes or TICI scores. There was a significant difference in the mRS after the 1st and 2nd events (p = 0.014) but no significant difference if the 2nd event occurred contralateral to the 1st event (p = 0.66) (n = 22). It is therefore concluded that recurrent thrombectomy can be safely performed with no significant difference in the technical aspects of the procedure.